Mission PCOSsible: a campaign to raise awareness of polycystic ovary syndrome in Singapore - Chua, Cerise Wan Ni (Nanyang Technological University, 2024)
This paper presents Mission PCOSsible, a health communications campaign to increase awareness of Polycystic Ovary Syndrome (PCOS) among women in Singapore and encourage early medical intervention if exhibiting symptoms. Despite its global prevalence affecting 10% of females, around 70% of cases remain undiagnosed, potentially leading to severe health risks. Key problems identified were: (1) lack of awareness and knowledge regarding PCOS, (2) limited conversations around PCOS contributing to limited knowledge and support avenues for individuals with PCOS, and (3) lack of confidence in identifying PCOS symptoms.